Pengaruh Perbedaan Kepadatan terhadap Kelangsungan Hidup Benur Udang Vaname (Litopenaeus vannamei) dalam Transporatasi Tertutup Selama 36 Jam - Mallombasi Mallombasi; Indra Wirawan; Maria Agustini (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2026)
Whiteleg shrimp (Litopenaeus vannamei) is one of the species that is a national superior commodity. The traffic of shrimp between provinces in Indonesia showed a significant increase in the period 2014-2017 with an average growth of 74.48% per year. Things that need to be considered in distribution activities are determining the number of seeds to be transported, providing oxygen in the packaging container, optimizing the use of low temperatures to suppress metabolic activity. This study was conducted with the aim of determining different densities on survival and determining the optimal density for the survival of whiteleg shrimp (Litopenaeus vannamei) in closed transportation for 36 hours. The method in this study used an experimental method with data collection carried out through direct observation. The experimental design used in this study was a Completely Randomized Design (CRD) with 5 treatment combinations. Density consisted of 1500 individuals/2 liters, 2000/2 liters, 2500 individuals/2 liters, 3000/2 liters and 3500 individuals/2 liters. The main parameters observed were survival and the test parameters measured were DO, temperature, salinity, and pH. The results showed that the best performer was in Treatment (B) with a density of 2,000 individuals with a survival rate of 86.02%. The results of the air quality observation study showed that almost all were still at optimal levels to support the survival of whiteleg shrimp (Litopenaeus vannamei) with an average temperature of 26.22°C. pH 7.18 – 8.08. Dissolved oxygen 3.87 – 8.06 ppm.